A longitudinal time and motion study quantifying how implementation of an electronic medical record influences hospital nurses' care delivery. (September 2021) - Bingham, Gordon; Tong, Erica; Poole, Susan; Ross, Paul; Dooley, Michael
Abstract: Aim background: Many health care services are implementing or planning to undergo digital transformation to keep pace with increasing Electronic Medical Record (EMR) functionality. The aim of this study was to objectively measure nursing care delivery before and following introduction of an EMR. Design and methods: An extensive program of work to expand an EMR across our health service using a 'big bang' methodology was undertaken. The program incorporated digital care delivery workflows including physiological observations, clinical notes and closed loop medication management. The validated Work Observation Method by Activity Timing (WOMBAT) method was applied to undertake a direct observational time and motion study of nurses' work in a major Australian hospital immediately prior to and six months following the introduction of a full clinical EMR. Results: Time and motion results were from observing approximately one week of nursing time pre (paper) to six months post (EMR) implementation. A non-significant 6.4% increase in the proportion of time spent on direct care was observed when using the EMR with a statistically significant increase in mean time per direct care task (2.5 min vs 3.9 min, p = 0.001). The proportion of time spent on medication-related activities did not significantly change although the average time per task rose from 2.0 to 2.9 min ( p = 0.008). A significant reduction in proportion of time spent in transit and indirect care tasks when using the electronic workflows was reported. No statistically significant changes to the proportions of time spent on professional communication, direct care or documentation were observed. Conclusions: Successful EMR implementation is possible without adversely affecting allocation of nursing time. Our findings from deploying a large scale EMR across all healthcare craft groups and workflows have described for nurses that an EMR enables them to spend longer with patients per direct care episode and use their time on other activities more effectively.